Hashimoto's thyroiditis predicts outcome in intrathyroidal papillary thyroid cancer. Issue 9 (September 2017) - Marotta, Vincenzo; Sciammarella, Concetta; Chiofalo, Maria Grazia; Gambardella, Claudio; Bellevicine, Claudio; Grasso, Marica; Conzo, Giovanni; Docimo, Giovanni; Botti, Gerardo; Losito, Simona; Troncone, Giancarlo; De Palma, Maurizio; et al.
Abstract : Hashimoto's thyroiditis (HT) seems to have favourable prognostic impact on papillary thyroid cancer (PTC), but data were obtained analysing all disease stages. Given that HT-related microenvironment involves solely the thyroid, we aimed to assess the relationship between HT, as detected through pathological assessment, and outcome in intrathyroidal PTC. This was a multicentre, retrospective, observational study including 301 PTC with no evidence of extrathyroidal disease. Primary study endpoint was the rate of clinical remission. Auxiliary endpoint was recurrence-free survival (RFS). HT was detected in 42.5% of the cohort and was associated to female gender, smaller tumour size, lower rate of aggressive PTC variants and less frequent post-surgery radio-iodine administration. HT showed relationship with significantly higher rate of clinical remission ( P  < 0.001, OR 4, 95% CI 1.78–8.94). PTCs with concomitant HT had significantly longer RFS, as compared with non-HT tumours ( P  = 0.004). After adjustment for other parameters affecting disease outcome at univariate analysis (age at diagnosis, histology, tumour size and multifocality), prognostic effect of HT remained significant ( P  = 0.006, OR 3.28, 95% CI 1.39–7.72). To verify whether HT could optimise the identification of PTCs with unfavourable outcome, we assessed the accuracy of 'non-HT status' as negative prognostic marker, demonstrating poor capability of identifying patients not maintaining clinical remission until final follow-up (probability of no clinical remission in PTCs without HT: 21.05%, 95% CI 15.20–27.93). In conclusion, our data show that HT represents an independent prognostic parameter in intrathyroidal PTC, but cannot improve prognostic specificity.